Improvise the truth.Jazz music and philosophical discourse (Itinera, 2015)
Improvisation is specific of some arts, like jazz music, but, as a practice, it is part of almost all complex human practices, included the professional ones, because of the role it plays in transforming and developing them. Improvisation plays an important role even in philosophical discourse, whose process is comparable with the jazz music process. However, in both fields a circularity arises, which creates a problem concerning the validity and the normativity of their whole processes. A reflection on the two fields suggests some possible solution paths.